Working with adoptive parents : research, theory, and therapeutic interventions - Brabender, Virginia; Fallon, April (Wiley, 2013)
"Editors Virginia Brabender and April Fallon are clinical psychologists and also adoptive parents whose families are acquainted with both the uncertainty and joy of adoption. In Working with Adoptive Parents, they offer an in-depth treatment of the distinctive needs, feelings, impulses, expectations, and conflicts that adoptive parents experience through the stages of adoption and beyond. This volume offers a comprehensive picture of adoption through an exploration of the experiences and developmental processes of the adoptive parent. Providing a framework for therapists to conceptualize their work with adoptive parents, Working with Adoptive Parents clarifies and facilitates the journey that many of these families face."--Publisher's website.